PENERAPAN HIDROPHOBYC DRESSING DAN SALEP EPITEL CREAM UNTUK PENYEMBUHAN LUKA PADA PASIEN ABSES DI PRAKTIK MANDIRI GRIYA AFIAT KOTA MAKASSAR - Wina Eka Cahyani; Nur wahyuni Munir; Wa Ode Sri Asnaniar; Nurwahidah (Jurnal Kesehatan, 2025)
An abscess is a skin infection caused by the accumulation of pus, often due to Staphylococcus aureus, and is more common in patients with diabetes mellitus due to immune and microcirculation disorders. Conventional treatment is often limited in controlling exudate and preventing infection, thus requiring modern dressing alternatives. This study employed a descriptive method with a case study approach on abscess wound patients at Griya Afiat Private Practice in Makassar City, applying modern Hydrophobic dressing and zinc epithelial cream to assess the effectiveness of treatment in accelerating healing. The case study was conducted on a 56-year-old female patient, Mrs. R, with a back abscess, through wound cleaning, application of Hydrophobic, and epithelial cream on the periwound. After two treatments, the wound area decreased from 1.4 cm² to 0.49 cm², exudate decreased from 25% to 15%, granulation tissue increased from 60% to 65%, and epithelialisation increased from 15% to 25%, indicating an active proliferation phase. The patient also reported increased comfort and no signs of infection were found. The application of hydrophobic dressing (Cutimed Sorbact) combined with Zinc Cream Epitel proved effective in accelerating the healing process of abscess wounds. The results of this case study are expected to serve as a reference in wound care nursing practice and additional literature for the development of nursing science in the field of wound care.